Characterisation of the HIV-1 reservoir and the potential for viral eradication - Williams, J; James Williams (2014)
The HIV-1 reservoir is the major barrier to eradication and cure of HIV-1 infection. The aim of this thesis was to characterise the HIV-1 reservoir in PHI and to investigate two potential reservoir clearance strategies. Sensitive Q-PCR assays that quantify HIV-1 DNA reservoir level were developed and applied to characterise the HIV-1 reservoir in acutely infected patients enrolled in the SPARTAC trial. HIV-1 DNA levels were found to be a useful biomarker for predicting clinical progression and the time of viral remission in patients, after HAART interruption. Since low HIV-1 DNA reservoir levels were clinically beneficial, potential therapies aimed at decreasing the reservoir burden were investigated. Thermotherapy was employed as a possible method for increasing CTL killing ability of HIV-1-infected cells. This may increase the likelihood of virological control and functional cure. SPION uptake impacted negatively on the natural killing ability of CTL that expressed the high affinity 868-TCR. However, localised thermotherapeutic heat generation was insufficient to cause direct thermal ablation of bound target cells or to enhance the natural killing ability of CTL. 868-TCR transduced CTL were employed directly as a means to target the latent viral reservoir by the ‘kick and kill’ hypothesis. Latent HIV-1 was reactivated in a variety of latent cell line models, but inconclusively in a primary model. 868-TCR transduced CTL killing of latently infected cells was observed. However, reactivation of latent virus did not necessarily relate to increased antigenicity of latent cells, perhaps in part due to anti-latency drug-induced alterations in MHC class I expression. Despite recent and sustained interest in HIV-1 cure strategies, the prospect still remains elusive. Only through the development of sensitive assays that measure the HIV-1 reservoir and their application to novel and innovative cure strategies will HIV-1 ever be functionally cured or eradicated in patients on a large scale.